Sperm surface proteins in mammalian fertilization - Jonáková, V; Manásková, P; Kraus, M; Liberda, J; Tichá, M (Molecular reproduction and development, 2000)
Boar seminal plasma was separated into five protein fractions (I-V) (> 100, 55, 45, 30, 5-15 kDa) by gel chromatography on Sephadex G-75 SF at pH 7.2. RP-HPLC of protein fractions I-V and N-terminal sequencing of their individual components revealed that the high-molecular-weight aggregates consisted mainly of DQH sperm surface protein and AQN, AWN, PSP II spermadhesins, whereas fraction IV consisted of heterodimers of PSP spermadhesins only. Spermadhesins as monomers were present in seminal plasma in a very low amount. Aggregates containing the DQH protein and AWN spermadhesins as well as HPLC-separated monomeric proteins interacted strongly with acidic polysaccharides. The strongest interaction was observed between biotinylated glycoproteins of porcine zona pellucida and AWN 1-containing aggregates and separated proteins. PSP II interacted with some acidic polysaccharides, whereas the fraction IV corresponding to heterodimer PSP I/PSP II did not show any binding to acidic polysaccharides and zona pellucida. Aggregates containing AWN, AQN, DQH, PSP II proteins, and their separated monomeric forms (fractions I-III) interacted with phosphorylcholine. Fractions I-III showed affinity to cholesterol. Biotinylated aggregates containing AWN, AQN, DQH, and PSP proteins (fractions I-IV) bound stronger to boar epididymal spermatozoa than to ejaculated spermatozoa. These results suggest that under physiological conditions, the aggregates of seminal plasma proteins (DQH, AQN, AWN, PSP II) rather than the individual proteins might take part in coating the sperm surface, in sperm capacitation, and in primary binding of spermatozoa to zona pellucida of the ovum.
Keywords: Chromatography, High Pressure Liquid; sperma; Membrane Proteins; gelová chromatografie; spermie; fertilizace; sekreční proteiny semenných váčků; Seminal Vesicle Secretory Proteins; zvířata; Membrane Glycoproteins; membránové glykoproteiny; transportní proteiny; Swine; Cell Adhesion Molecules; Carrier Proteins; Fertilization; glykoproteiny; Seminal Plasma Proteins; Male; Glycoproteins; molekuly buněčné adheze; Semen; membránové proteiny; proteiny semenné plazmy; Spermatozoa; Animals; mužské pohlaví; Chromatography, Gel; vysokoúčinná kapalinová chromatografie; prasata